GROSS AND HISTOMORPHOMETRIC STUDY OF FORESTOMACH OF JATTAL AND NACHI GOAT BREEDS - Sana Khurshid; Hafsa Zaneb; Sahar Ijaz; Ali Fakharuddin; Abid Hussain; Syeda Fakhra Waheed; Muhammad Ali; Samia Mushtaq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The digestive mechanism of goats, particularly the forestomach, allows converting low-quality forages into high-nutritional-value products. As a result, understanding the functional architecture of the forestomach is critical since it is intimately involved with the conversion of food to valuable products like as milk and meat.  A total of 30 goats, 15 each of the Nachi and Jattal breeds, were chosen from the slaughter house, the Punjab Agriculture and Meat Company (PAMCO), Lahore, Pakistan for this investigation. All of the animals were between the ages of 1 and 2 years. The rumen was sampled from five distinct sites including cranial, dorsal, ventral sac, caudo-dorsal blind sac, and caudo-ventral blind sac. Omasal specimens were collected from several areas including reticulo-osamal, middle omasal, and omaso-abomasal junction. For the reticulum, samples were obtained from the medial wall of the reticulum. The data was analysed using an unpaired T-test through SPSS 20.0 software. The level of significance was p≤0.05. The results showed that there was a significant difference in gross anatomical and histomorphometric parameters of rumen, reticulum and omasum of Nachi and Jattal breeds. However, in gross anatomical parameters, more relative weight of filled rumen and omasum was found in Jattal breeds. İn histomorphometric parameters,  muscularis thickness, papillae length, thickness of keratinized epithelial layer and total epithelial thickness of rumen was more in Nachi breeds. İt was concluded that Gross anatomical features of forestomach in Nachi breed are greater than those of Jattal breed. However, histomorphometric parameters are greater in Jattal than in Nachi breed. This study will assist to differentiate the anatomical and histomorphometric parameters of Jattal and Nachi goat breeds from other analogous small ruminants.